Integrated solution for future transportation and power systems through wind-solar hybrid power plant with energy storage - Thananjeyan, S.; Arunan, S.; Thiruvaran, T.; Atputharajah, A.; Ramachandaramurthy, V.K. (My University, 2014)
This paper addresses integrated solutions with the energy storage, which plays multiple roles in applications in transportation and power systems. The proposed integrated and automated control concept for a battery charging station, which can be also used for electric vehicle applications, improves the performance of solar power plant while effectively using the power systems network. This has number of benefits such as: (i) eliminates power fluctuations in the grid, which generated due to intermittent nature of solar intensity or wind speed, and allows to increase renewable energy penetration (ii) charge the batteries by absorbing all fluctuating active power components, which eliminates voltage flicker at the grid, (iii) allow facility for load shifting, (iv) allow grid voltage or reactive power control if it is required by the system operator and (v) finally fast charging of battery is also possible when ever need arises. This coordinated control technique helps to utilize the power electronic devices together with energy storage to achieve number of operations together or separately. Therefore it is called as all-in-one-device concept in this paper. This is an excellent value addition for any of the existing power electronic converters already used especially in solar power generation. Further this is going to be the trend with (i) boosting electric vehicle technology for transportation and (ii) viable solar power plant technology, where energy storages are commonly applied.
Keywords: Solar power plant; battery charging control